Post-pericardiotomy syndrome: insights into neglected postoperative issues. (21st October 2021) - Maranta, Francesco; Cianfanelli, Lorenzo; Grippo, Rocco; Alfieri, Ottavio; Cianflone, Domenico; Imazio, Massimo
Abstract: : Abstract OBJECTIVES: Pericardial effusion is a common complication after cardiac surgery, both isolated and in post-pericardiotomy syndrome (PPS), a condition in which pleuropericardial damage triggers both a local and a systemic inflammatory/immune response. The goal of this review was to present a complete picture of PPS and pericardial complications after cardiac surgery, highlighting available evidence and gaps in knowledge. METHODS: A literature review was performed that included relevant prospective and retrospective studies on the subject. RESULTS: PPS occurs frequently and is associated with elevated morbidity and significantly increased hospital stays and costs. Nevertheless, PPS is often underestimated in clinical practice, and knowledge of its pathogenesis and epidemiology is limited. Several anti-inflammatory drugs have been investigated for treatment but with conflicting evidence. Colchicine demonstrated encouraging results for prevention. CONCLUSIONS: Wider adoption of standardized diagnostic criteria to correctly define PPS and start early treatment is needed. Larger studies are necessary to better identify high-risk patients who might benefit from preventive strategies. Abstract : Pericardial complications after cardiac surgery are common but under-reported conditions that increase morbidity with a great impact on postoperative management.